Perceptions of the Efficacy of Classroom Management Techniques - Mehler, Philip R. (Journal of the American Academy of Special Education Professionals, 2022)
One of the biggest challenges of teaching is classroom management. This paper covers some of the abundant literature that has been written on the topic, with the goal of narrowing down the practices to a short list that can be used in practice by aspiring or current teachers. After reviewing the literature, with a focus on that produced within the last five years, the author sought feedback from actual teachers to obtain more direct perceptions of classroom management tactics from those vested in the field. A thirty question Google Survey was provided to an engaged teacher Facebook Group. While over a dozen techniques were clearly being used to some level, a few stood out as being seen as most efficacious and thus should be prioritized within teachers’ classroom management repertoire: consistent routines, establishment of classroom rules or expectations, purposeful teacher movement, seating arrangements, and meeting the psychological needs of students.